Efficacy of Phototherapy With 308-nm Excimer Light for Skin Microbiome Dysbiosis and Skin Barrier Dysfunction in Canine Atopic Dermatitis - Park, Ju-Yong; Kim, Seon-Myeong; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2021)
The management of canine atopic dermatitis, an allergic skin disorder, is challenging. To examine the effect of phototherapy using a 308-nm excimer light as a topical treatment for canine atopic dermatitis, 10 dogs with canine atopic dermatitis and 10 dogs with healthy skin were enrolled in this study. Phototherapy was applied every seven days for a total of two months. The skin microbiome, skin barrier function, and clinical outcomes were evaluated after phototherapy. Phototherapy significantly changed the composition of the skin microbiome in canine atopic dermatitis and significantly increased the relative abundance of the phyla Actinobacteria and Cyanobacteria. It significantly alleviated clinical signs of canine atopic dermatitis without serious adverse effects. Transepidermal water loss, as a measure of skin barrier function, significantly decreased after phototherapy. In addition, phototherapy increased microbial diversity and decreased the relative abundance of Staphylococcus pseudintermedius, a superantigen in atopic dermatitis. These results suggest that excimer light therapy is an effective and safe therapeutic option for canine atopic dermatitis, which is also a spontaneous animal model of atopic dermatitis